2017
DOI: 10.1016/j.infbeh.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

A developmental perspective on the neural bases of human empathy

Abstract: While empathy has been widely studied in philosophical and psychological literatures, recent advances in social neuroscience have shed light on the neural correlates of this complex interpersonal phenomenon. In this review, we provide an overview of brain imaging studies that have investigated the neural substrates of human empathy. Based on existing models of the functional architecture of empathy, we review evidence of the neural underpinnings of each main component, as well as their development from infancy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 69 publications
0
40
0
6
Order By: Relevance
“…Empathy can be considered as an 'umbrella' term that encompasses all processes that emerge, so an observer could understand the "other's" state by activating their own neural and mental representations of that state. In this view, empathy is a multicomponent process that encompasses cognitive processes, such as mentalizing or emotional regulation, and affective processes such as empathic concern or emotional detection, to name a few (de Waal & Preston, 2017;Decety, 2011;Tousignant et al, 2017;Zaki & Ochsner, 2012). Taking into account the nature of sub-processes that are involved in the empathic response, it is easy to address empathy as a personalized phenomenon which response can be regulated.…”
Section: Introductionmentioning
confidence: 99%
“…Empathy can be considered as an 'umbrella' term that encompasses all processes that emerge, so an observer could understand the "other's" state by activating their own neural and mental representations of that state. In this view, empathy is a multicomponent process that encompasses cognitive processes, such as mentalizing or emotional regulation, and affective processes such as empathic concern or emotional detection, to name a few (de Waal & Preston, 2017;Decety, 2011;Tousignant et al, 2017;Zaki & Ochsner, 2012). Taking into account the nature of sub-processes that are involved in the empathic response, it is easy to address empathy as a personalized phenomenon which response can be regulated.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the neural substrates of empathy in healthy populations is important for understanding conditions that are characterised by empathic difficulties. In neuroscience, the concept of empathy is considered to include separate affective (sharing others' emotion) and cognitive (understanding others' emotion) components (for example, Tousignant et al., 2017 ; Lockwood, 2016 ). Previous research has identified distinct clusters of brain regions involved in affective empathy: medial/anterior cingulate cortex (MCC, ACC), anterior insula (AI) ( Fan et al., 2011 ; Lamm et al., 2011 ), and supplementary motor area (SMA) ( Lamm et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional empathy, by contrast, is more primitive in nature and rooted in subcortical arousal. 6 This type of empathy is spontaneous and involves the contagious experience of another person's affective state. 5 Evidence in psychopathology 7,8 and neurology 9 suggests a dissociation between cognitive and emotional empathy, as some individuals can show impairment in one system and intact ability in the other.…”
mentioning
confidence: 99%